Innovative Investment Concept as an Instrument for Pension Plan and Asset Protection - Bergold, Uwe (2019)
Due to the fact that we are currently in an epochal global debt crisis and at the same time, as a result, in an "all bubble", it is becoming increasingly difficult for investors to survive the coming years without losses. The innovative investment concept presented in this paper plays an important role as an instrument for old-age provision and asset protection. Even though there are no guarantees on the capital market and the future cannot be predicted, the results of the systematic concept show that the consideration of macroeconomic boom and bust phases by a strategic investment concept generates a significant outperformance compared to a passive buy-and-hold strategy. On the other hand, it also represents an asset protection concept in bust phases.